Assessing the impact of the financial condition on the components of sustainable development of transport enterprises in Poland in 2008-2019 - Misztal, Anna (Ocena wpływu kondycji finansowej na komponenty zrównoważonego rozwoju przedsiębiorstw transportowych w Polsce w latach 2008-2019)
The sustainable development of an enterprise includes the implementation of the economic, social, and environmental goals. In business practice, this means taking actions to maximize profits while implementing social and ecological tasks. The article’s primary goal is to assess the impact of the financial condition on the components of sustainable development of transport companies in Poland in 2008-2019. A company’s sustainable development is understood here as achieving the intended economic, social, and environmental results. The primary method used in the study is the Ordinary Least Squares (OLS) method, which allowed for the estimation of three equations in which the endogenous variables are economic (ED), social (SD) and environmental development (EnvD). According to the estimation results, the individual components are interdependent. The financial condition (FC) for the current period and the previous one impact on economic and social development, while environmental development depends on its financial situation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 1, s. 129-143